Konsep Pemikiran Ekonomi dan Maqashid Syariah Perspektif Imam Al-Syathibi - Dede Nurwahidah; Yadi Janwari; Dedah Jubaedah (Yayasan Literasi Sains Indonesia, 2024)
Imam Al-Syathibi is one of the leading figures in the field of ushul fiqh and maqshid sharia. al-Syathibi emphasized that all Islamic sharia law aims to create benefits for humans, both in this world and in the afterlife. According to Imam al-Syathibi, maqashid sharia consists of three levels, namely dharuriyah, hajiyat, and tahsiniyat. This research aims to examine the history of economic thought on the concept of maqashid sharia according to Imam Al-Syathibi. Using a qualitative approach and literature study methods, this research analyzes primary and secondary sources related to Imam Al-Syathibi's thoughts. The results of the research show that Imam Al-Syathibi's thoughts regarding Maqashid Syariah are very comprehensive, so that the aim of this thinking is to obtain benefits in the world and the hereafter, thus the concept of Maqashid Syariah becomes a guide in the development and implementation of Islamic law in accordance with the principles of monotheism, justice, Benefits and balance of needs, namely religion (Din), soul (Nafs), reason ('Aql), heredity (Nashl), and wealth (Mal). and comprehensive in understanding and applying Islamic law, by combining textual interpretation and contextual considerations as well as maqashid sharia. The idea about basic needs put forward by Al-Syathibi is more universal when compared to Abraham Maslow's theory, namely the hierarchy of needs theory, namely physiological needs, security needs, social needs, esteem needs and self-actualization needs.